Evaluation of flood disaster management planning: a comparative method for Bostwana and Indonesia - Gunanda, Arkha; Koestoer, Raldi Hendrotoro Seputro (ASEAN Natural Disaster Mitigation and Education Journal, 2023)
Disaster management planning is an activity that is translated into documents to be used as a reference in carrying out disaster risk reduction.. Furthermore, based on data from UN-ESCAP for 2022, disaster events in Indonesia dan Bostwana are dominated by extreme weather, especially storms, floods and droughts. so that disaster management planning, especially for flood disasters, is considered important as one of the efforts to reduce disaster risk. This study aims to compare the evaluation results of the disaster management planning documents owned by Botswana and Indonesia. This study uses a systematic literature review method and a comparative study with a qualitative descriptive approach to evaluation of disaster management planning between Gaborone, Botswana and Yogyakarta, Indonesia. The results of the research show that the evaluation of disaster management planning in Gaborone City, Botswana still requires updating and involving the public more in the preparation of this document. In addition, the results of the evaluation of disaster management planning documents in the City of Yogyakarta, Indonesia still require efforts to integrate disaster documents with other planning documents so that they can become a reference for the implementation of disaster risk reduction activities by various stakeholders involved in the disaster sector. The problem with disaster management planning documents in the two countries is the lack of public involvement and the lack of integration of this disaster management planning document with other development planning documents, including issues regarding validity periods. The offered solution is to update the disaster management planning document by involving more public argument.